The Comparative Analysis of the Microbial Communities of Activated Sludge - Sipos, Dóra; Miseta, Roland; Zseni, Anikó (International Journal of Engineering and Management Sciences, 2018)
The composition of the microbial communities in the activated sludge was thought mostly chaotic and unpredictable, but due to the new studies and breakthroughs in the past decades, now it is known that specific, accidental and non-accidental factors are responsible for the structure of the microbial community. The aim of the study is to compare the microbial communities of activated sludge of one large and two small wastewater treatment plants. During our research 14 months of data were processed. After the sample analysis and data processing, the diversity and seasonal changes of the community structures revealed. The results of the statistical analysis show that the larger system has more diverse community structure.